Altering Perceptions, Visualizing Sub-ground Metal Objects - Aleksander Pedersen (Emerging Science Journal, 2020)
Smart phones and sensor technology represent a key part of everyday life and are being used in areas such as safety, training, healthcare and others. Utilizing an array of internal sensors and a metal detector requires an evaluation of the precision of the measurements and performance reviews. Metal detectors are versatile, with uses in healthcare as well as recreational, but a common issue often seen in the proprietary equipment is bad presentation of data. Usually the user interface is just numbers on a display, simplified graphs or sounds. By combining smartphone sensors with a metal detector and a custom mount we model a mapping between the virtual and physical model, a digital twin. In this paper we are utilizing the computing capabilities of a smartphone and employing visualization techniques not possible by partial information. In addition, we present an improved graphical user interface without any proprietary accessories. For this purpose, preliminary case studies are included as a part of a prototype in development.